A Blind Blur Detection Scheme Using Statistical Features of Phase Congruency and Gradient Magnitude. (15th July 2014) - Tiwari, Shamik; Shukla, V. P.; Biradar, S. R.; Singh, A. K.
Abstract : The growing uses of camera-based barcode readers have recently gained a lot of attention. This has boosted interest in no-reference blur detection algorithms. Blur is an undesirable phenomenon which appears as one of the most frequent causes of image degradation. In this paper we present a new no-reference blur detection scheme that is based on the statistical features of phase congruency and gradient magnitude maps. Blur detection is achieved by approximating the functional relationship between these features using a feed forward neural network. Simulation results show that the proposed scheme gives robust blur detection scheme.